Brief Reports - SWOG S0709: Randomized Phase II Trial of Erlotinib versus Erlotinib Plus Carboplatin/Paclitaxel in Patients with Advanced Non–Small Cell Lung Cancer and Impaired Performance Status as Selected by a Serum Proteomics Assay. Issue 3 (March 2016) - Lara, Primo N.; Moon, James; Hesketh, Paul J.; Redman, Mary W.; Williamson, Stephen K.; Akerley, Wallace L.; Hirsch, Fred R.; Mack, Philip C.; Gandara, David R.
ABSTRACT : Introduction: : Patients with advanced‐stage non–small cell lung cancer (NSCLC) and borderline performance status (performance status 2 [PS2]) are often excluded from clinical trials and platinum‐based therapy. In light of the potential role for serum proteomics in predicting the benefit of erlotinib beyond that of epidermal growth factor receptor gene ( EGFR ) mutational status, we conducted a trial in which the Veristrat proteomics assay was used for data enrichment when selecting a cohort of patients with NSCLC and PS2 to receive erlotinib with and without chemotherapy. Methods: : Patients with metastatic NSCLC, PS2, acceptable end‐organ function, and Veristrat‐good status were randomly assigned to receive either 150 mg of erlotinib orally daily (arm 1) or 150 mg of erlotinib orally daily on days 2 through16 plus four cycles of carboplatin (area under the curve = 5 on day 1) and paclitaxel (200 mg/m 2 intravenously on day 1) followed by 150 mg of erlotinib orally (arm 2). The arm 2 agents were pharmacodynamically separated to mitigate potential antagonism. The arm with superior observed median progression‐free survival (PFS) would be selected for further evaluation, but only if PFS lasted for at least 3 months. Results: : The trial terminated before the planned accrual of 98 patients for regulatory reasons. A total of 156 patients were screened. Of the 83 (59%) who were classified as Veristrat good, 59 met the trial eligibility criteria and were randomly assigned to one of two arms (33 patients in arm 1 and 26 in arm 2). The patients in arm 2 patients had a higher response rate (23% versus 6%, p = 0.06), disease control rate (77% versus 41%, p = 0.0046), median PFS (4.6 versus 1.6 months, p = 0.06), and median overall survival (11 versus 6 months, p = 0.27). Treatment‐related grade 4 adverse events were seen in two patients in arm 1 (thrombosis and hypomagnesemia) and in five patients in arm 2 (neutropenia in five, febrile neutropenia in one, and leukopenia in one). Conclusions: : In a proteomics‐enriched cohort of patients with NSCLC and PS2, pharmacodynamically separated erlotinib plus chemotherapy had better efficacy than did erlotinib alone and surpassed the protocol‐specified benchmark of PFS of at least 3 months required for further study.